INVESTIGATING ON THE EIGHTH SEMESTER STUDENTS’ ERRORS ON READING SKILLS FOR TOEFL AT ENGLISH STUDY PROGRAM FKIP RIAU UNIVERSITY - Yeni Fitriani; Erni Erni; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aimed to investigate the eighth-semester students’ dominant errors on reading skills for TOEFL at English Study Program FKIP Riau University. The eighth-semester students of the English Study Program in the academic year 2020/2021 were the population of this research. Eighty six samples were selected using the proportional random sampling technique. This quantitative research used the Reading TOEFL Test as an instrument that was distributed via Google – form. The test consisted of 50 questions adopted from the TOEFL Best Preparation book by Shania Kaitlyn and Thomas Logan. The data from the Google form was analyzed to determine dominant errors by observing the number of wrong answers in each reading skill. This research revealed that the dominant errors on reading skills for TOEFL made by the eighth semester were the first on skill IV Implied Detail Question the percentage of error was 61.40%. Second, was on skill I Main Idea Question, with 58.47% of errors, and then skill II Stated Detail Question with 46.03% of errors.Key Words: Investigating, Errors, Reading Skills, TOEFL.